2022
DOI: 10.1021/acs.jafc.2c02742
|View full text |Cite
|
Sign up to set email alerts
|

TMT-Based Quantitative Proteomics Analyses Reveal the Antibacterial Mechanisms of Anthocyanins from Aronia melanocarpa against Escherichia coli O157:H7

Abstract: Aronia melanocarpa anthocyanins (AMAs), as natural plant extracts, can control pathogens and are attracting increasing attention. In this study, a tandem mass tag (TMT) quantitative proteomics method combined with multiple reaction monitoring (MRM) was used to explore the antibacterial mechanism of AMAs against Escherichia coli at the protein level. The results showed that 1739 proteins were identified in E. coli treated with AMAs, of which 628 were altered, including 262 downregulated proteins and 366 upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The proteomics method was carried out according to the previous description. 21,22 In brief, E. coli O157:H7 cells were added with lysis buffer and centrifuged to obtain the supernatant. DTT was added to the sample, and iodoacetamide was added after a water bath at 56 °C for 1 h. 30 μg of the sample was added to the ultrafiltration tube, and the waste liquid was discarded after centrifugation.…”
Section: Proteomics Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The proteomics method was carried out according to the previous description. 21,22 In brief, E. coli O157:H7 cells were added with lysis buffer and centrifuged to obtain the supernatant. DTT was added to the sample, and iodoacetamide was added after a water bath at 56 °C for 1 h. 30 μg of the sample was added to the ultrafiltration tube, and the waste liquid was discarded after centrifugation.…”
Section: Proteomics Analysismentioning
confidence: 99%
“…Previous reports have shown that AMAs can enter Escherichia coli O157:H7 cells through the bacillary mechanosensitive channel and affect the expression of proteins involved in oxidative stress, protein biosynthesis, DNA replication and repair and other processes. 21,22 Furthermore, metabolomics and proteomics data were integrated. First, the pathway results were classified and analyzed, including metabolism, environmental information processing, cellular processes, human diseases, and genetic information processing.…”
Section: Integration Of Proteome and Metabolomementioning
confidence: 99%
“…However, the overuse of antibiotics in cultivating fishery and clinical treatment resulted in antibiotic resistance. 8 In recent years, compounds of natural origins with antimicrobial activity have attracted growing interest of researchers. These substances are often recognized as safe or low-toxic and are less likely to induce drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Proteomics and metabolomics are effective approaches to investigate the changes of proteins and metabolic profiles in bacteria caused by environmental stress, and which have been extensively used to elucidate the antimicrobial mechanism of natural compounds. 8,19,20 In this study, the minimum inhibitory concentration (MIC) value, intracellular ATP concentration, membrane permeability, and ultrastructure changes were determined to assess the antibacterial effect of hexanal against V. parahaemolyticus. TMT-based quantitative proteomics and non-targeted metabolomics were performed to reveal the associated mode of action of hexanal against V. parahaemolyticus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation